The Implementation Of Linguistic Intelligence In Teaching Speaking Through Audio-Visual - Nila Sari Dewi; Juni Hartiwi; Nurul Ari Yani; Sri Sutiwi (Journal on Education, 2023)
The research aims to describe; (1) the process of teaching speaking by using audio visuals, (2) the problems that appeared and its solution in implementing linguistic intelligence for teaching speaking through audio-visuals, and (3) the improvement of students speaking skills. The method used was Classroom Action Research, which involved students in the third semester of the Foreign Language Academy of Dian Cipta Cendikia Bandar Lampung. This action research consisted of 2 cycles. In the first cycle, students did activities such as listening to the songs in audio, reading the song's text and understanding the song's lyrics, and practicing speaking individually. In the second cycle, students did activities such as listening to the song in audio and visual, reading and understanding the song lyrics using word functions (noun, verb, adj., and adv.), and practicing speaking in pairs. The data were from students, teachers, and test observations. The findings indicated that; (1). There was an improvement in active students in learning activities; first cycle, 2D3-BIa class had 50% active students in the first meeting and 65% active students in the second. There was an improvement for active students in the second cycle. 2D3-BIa class had 70% active students in the first meeting and 85% active students in the second. It means that the data had reached a minimum indicator of 70%, and (2) problems that appeared during the implementation of the teaching-learning process happened in pronouncing words, understanding words function, and expressing the idea of the content of the song's text. The solution was that the teacher should help all the students' problems to develop speaking skills repeatedly, and 3) the improvement of students' speaking skills was significant. In the first cycle, students who passed the test were 60%. There was an improvement in the second cycle. Students who passed the test were 85%. It means that the data had reached the minimum indicator.